The Effects of Multidisciplinary Collaborative Care Program on Depressive Prevention Amongst Diabetic Mellitus Type 2 Patients at a Secondary Level Hospital in Phetchaburi Province - สุขอร่าม, สิริรัตน์; นิมิตรอานันท์, นงพิมล; รุจนเวช, ศศิธร (Journal of The Royal Thai Army Nurses, 2018)
This research was a quasi-experimental research, two group pretest - posttest design aimed to study the effects of multidisciplinary collaborative care program on depressive prevention amongst Diabetic Mellitus (DM) type 2 patients who had risk of depression.The total 36 subjects divided into 2 groups; 17 subjects for experimental group and 19 subjects for comparison group.The experimental group was invited to join in a 10-week multidisciplinary collaborative care program. This program consisted of participatory group learning, relaxation skill training, group counseling, and telephone visit monitoring. Data were collected using psychological self – care behavior and diabetes- related stress. The reliability were presented at 0.86 and 0.85 respectively.The Mann-Whitney U test and Wilcoxon Signed Rank test were used for data analysis. The research results revealed that after the intervention, the experimental group had significantly better psychological self – care behavior score than those before the experiment and than the comparison group. (p value < .05) while they had significantly lower the diabetes- related stress score than before experiment and in the comparison group. (p value < .05) The researcher suggested that the multidisciplinary collaborative care program was effectively improved psychological self – care behavior and decreased stress among the diabetic patients. This program should be used in integrating healthcare services for depressive prevention in diabetic patients and other chronic diseases in other community hospitals.